Teachers' Perceptions and Experiences of Navigating Continuing Professional Development during the COVID-19 Pandemic - Tyrone Dempsey; Raj Mestry (MDPI AG, 2023)
Using social constructivism as a theoretical framework, we examined the perceptions and experiences encountered by South African teachers of their professional development during the COVID-19 pandemic. Translating teacher experiences into explicit learning contexts for learners remains an ongoing pedagogical challenge. For teachers to be effective, they must be prepared for changes and adapt swiftly to changing conditions. The need for pedagogical mobility to adopt a perspective of introspective teaching practice that engages learners in meaningful learning environments was crucial during the COVID-19 pandemic. Teachers were compelled to change their pedagogical approach; they were obliged to become digitally literate and apply advanced technology that would enable learners to access a wide range of activities and resources. Using a generic qualitative research design within an interpretivist paradigm, data were collected through semi-structured interviews with six teachers and analysed using Tesch's method of coding. We applied a generic qualitative methodology within an interpretivist paradigm to explore teachers' perceptions and experiences. Six teachers, purposefully selected from various schools, participated in this research. Our findings revealed that lack of guidance and support from educational authorities and school management teams negatively infringed on teachers' practice and professional development. However, teachers collaborated with peers and community members, engaged in knowledge-sharing, and adopted a trial-and-error approach to finding solutions. CPD programmes focusing on classroom management and pedagogical skills are highly recommended to foster the development of more proficient teachers.